2012
DOI: 10.1007/s11262-012-0826-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of influenza B viruses isolated in east-central China in 2009–2010

Abstract: The current circulating influenza B viruses can be divided into two major phylogenetic lineages: the Victoria and Yamagata lineages. We conducted a survey of influenza B viruses in Hubei and Zhejiang provinces during 2009-2010. Out of 341 throat swabs, 18 influenza B viruses were isolated. Five isolates were selected for genetic and phylogenetic analysis. The molecular analyses revealed that all the isolates had similar antigenic characteristics to B/Brisbane/60/2008. However, in the three viruses isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Furthermore, phylogenetic analysis of the NS gene showed that all viruses clustered together to form a distinct Lineage IV. The incongruent phylogenetic patterns observed at the lineage level corroborated with previous reports [ 7 , 13 , 15 , 16 ], which suggest that the phylogenies of eight gene segments could be divided into three distinct evolutionary profiles: (i) PB1, PB2 and HA genes derived from either Lineage II or III; (ii) PA, NP, NA and MP genes derived from Lineage II; and (iii) NS genes derived from Lineage IV. Firstly, the consistent grouping of Yam-like or Vic-like viruses in Lineage II or III, respectively, in the tree topology of PB1, PB2 and HA genes could be attributed to possible genetic linkage between these three gene segments, which has been described [ 8 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, phylogenetic analysis of the NS gene showed that all viruses clustered together to form a distinct Lineage IV. The incongruent phylogenetic patterns observed at the lineage level corroborated with previous reports [ 7 , 13 , 15 , 16 ], which suggest that the phylogenies of eight gene segments could be divided into three distinct evolutionary profiles: (i) PB1, PB2 and HA genes derived from either Lineage II or III; (ii) PA, NP, NA and MP genes derived from Lineage II; and (iii) NS genes derived from Lineage IV. Firstly, the consistent grouping of Yam-like or Vic-like viruses in Lineage II or III, respectively, in the tree topology of PB1, PB2 and HA genes could be attributed to possible genetic linkage between these three gene segments, which has been described [ 8 ].…”
Section: Resultssupporting
confidence: 89%
“…The phylogenetic trees reconstructed by the ML method for PB1, PB2, PA, HA, NP, NA, MP and NS genes are illustrated in Fig 1 and S3 Fig , which consist of selected Malaysian reassortants, WHO candidate vaccine and reference strains, as well as selected strains from other countries that were closely related to the selected Malaysian reassortants (≥99% sequence identities on all genes based on NCBI BLAST [ 26 ]). Consistent with other reports [ 7 , 13 , 15 ], the lineages for other genes (except for NS gene) were first assigned in the same manner as the HA gene, with lineages that resembled B/Yamagata/16/88-like viruses (Yam-like) designated as Lineage II, the lineages that resembled B/Victoria/2/87-like viruses (Vic-like) designated as Lineage III. The lineage that did not resemble any of the Vic- or Yam-like viruses was designated as Lineage IV (as for the case of NS gene) ( Fig 1 ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Both phylogenies indicate that all Malaysian Victoria viruses detected had Victoria-lineage HA and Yamagata-lineage NA. This inter-lineage reassortment has long been seen in B/Brisbane/60/2008-like viruses in previous studies [ 13 , 18 , 43 , 44 ], which were derived from B/Brisbane/32/2002-like viruses. They have a HA gene segment that evolved from B/Shangdong/7/97-like viruses of Victoria lineage and NA gene segment that evolved from B/Sichuan/379/99-like viruses of Yamagata lineage [ 39 ].…”
Section: Resultsmentioning
confidence: 53%
“…Residue 197 in the 190‐helix was changed from N to D in all sIBVs. This N197D mutation in N‐glycosylation motif (N‐X‐S/T) is associated with a loss of glycosylation site in HA1 and has been found in at least one of Taiwanese Victoria‐like human IBVs (B/Taiwan/2894/2006) in 2006/2007 season compared with B/Malaysia/2506/2004 vaccine, as well as 3 Zhejiang isolates of 2010 (B/Zhejiang/41/2010, B/Zhejiang/49/2010 and B/Zhejiang/429/2010) in China and 3 Italian Victoria‐like human IBVs (B/Milano/40NIC/2016, B/Milano/28CA/2016 and B/Milano/35CA/2016) compared with B/Brisbane/60/2008 vaccine. Several reports have demonstrated that egg‐adaptive mutations might lead to lost glycosylation .…”
Section: Discussionmentioning
confidence: 99%